Are cities losing innovation advantages? Online versus face-to-face interactions - GAETANI, Ruben (Institutional Knowledge at Singapore Management University, 2023)
How did COVID-19 affect the innovation advantages of dense locations? Using data on the universe of U.S. patent applications, we find that the density premium in the production of novel inventions declined by 18.5%-22.9% in 2020-2021 relative to its pre-pandemic level. Smartphone data on local mobility suggest that the drop in the frequency of local interactions can explain a significant portion of this effect. While COVID-19 resulted in a temporary setback in the innovation advantages of dense locations, the role of urban density in facilitating the exchange and recombination of ideas is unlikely to be persistently replaced by online communication.